Keefektifan Asap Cair dan Elektroterapi untuk Mengeliminasi Infeksi Xanthomonas oryzae pv. oryzae pada Benih Padi - Rizky G S Purnama; Kikin Hamzah Mutaqin; Efi Toding Tondok (Jurnal Fitopatologi Indonesia, 2018)
The Effectiveness of Liquid Smoke and Electrotherapy to Eliminate Infection of Xanthomonas oryzae pv. oryzae in Rice SeedBacterial leaf blight caused by Xanthomonas oryzae pv. oryzae is a seed-borne disease that can reduce the productivity of rice. Alternative treatments that have not been widely developed is application of liquid smoke and electrotherapy. The aim of this research was to study the effectiveness of liquid smoke and electrotherapy and their combinations to eliminate X. oryzae pv. oryzae without damaging seed quality. The study consisted of three experimental stages: (1) Liquid smoke treatment on the viability of the bacteria and rice seeds; (2) Electrotherapy treatment on the viability of bacteria and rice seeds; (3) Combination of liquid smoke and electrotherapy treatment in bacteria-infected rice seed. The results showed that liquid smoke concentration (5% for 30 minutes) was able to reduce 83.33% population of X. oryzae pv.oryzae on rice seeds with 94.33% seed vigor, 98.00% germination, and time required to achieve 50% of total seed emergence (T50) of 3.13 days. Electrotherapy treatment (400 mA for 20 minutes) was not only eliminated X. oryzae pv. oryzae on rice seeds up to 100% but also maintained seed vigor 81.67%, germination 89.33%, and T50 3.47 days. Electrotherapy treatment (400 mA for 20 minutes) followed by immersion of infected rice seeds in liquid smoke concentration (1% for 30 minutes) could reduce 94.59% bacteria population while maintaining 86.00% seed germination. Treatment of electrotherapy (400 mA for 20 minutes) followed by immersion seeds into liquid smoke concentration (5% for 30 minutes) could reduce bacterial population up to 100%, but caused phytotoxicity effect to the seedling.